Neuropathology of Autism - J Gordon Millichap (Pediatric Neurology Briefs, 2004)
The neuropathological literature and the prospects for future research in the genetics and pathology of autism are outlined in an inclusive review article from the University Medical Center Utrecht, The Netherlands.